Analysis of caesarean section practices and consequences in Goma, DR Congo: Frequency, indications, maternal and perinatal morbidity and mortality - Dikete Ekanga Michel; Prudence Mitangala; Yves Coppieters; Christine Kirkpatrick; Richard Kabuseya; Philippe Simon; Yvon Englert; Judith Racape; Wei-Hong Zang (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Introduction: Approximately 22.9 million Caesarean Sections (CS) are performed worldwide each year, mainly to save the life of the mother and/or new-born infant. However, with nearly 2 deaths in 1,000 live births, global neonatal mortality after CS is three times higher than after vaginal delivery. Nearly 300,000 women die every year as a result of a pregnancy or a caesarean or vaginal delivery. 99% of these maternal deaths occur in developing countries. Materials and methods: The study was conducted in the four referral hospitals in the city of Goma in DRC, between 01/11/2013 and 01/01/2016. Statistical analyses were performed using STATA/IC 15.0 for Windows. Univariate logistic regression was performed to determine which characteristics are associated with perinatal mortality. A value of p<0.05 was considered statistically significant. Results: The overall frequency of CS in the four facilities was 16.2%. Goma Provincial Hospital had the highest frequency. The three main indications for CS were dystocia, scarred uterus and foetal distress. The most frequent intraoperative complications were haemorrhage and injury to nearby organs (bladder and digestive tract), and the most frequent post-operative complications were wound infections, urogenital fistulae and hypertensive disorders. Our study describes a perinatal risk of 4.4%. Conclusion: Caesarean section should be a factor in reducing foeto-maternal morbidity and mortality if transfer conditions, working conditions at referral centre level, and health staff training are improved.